Pesticidal Activity of Citrus Fruits for the Development of Sustainable Fruit-Processing Waste Management and Agricultural Production - Hisashi Kato-Noguchi; Midori Kato (Plants)
The annual global production of citrus fruits is over 150 million tons, and 40–50% of the citrus fruits are processed into juices and other products. The processing generates a large amount of waste and causes environmental issues. In order to reduce the environmental impacts, several approaches for the waste management of citrus fruits were proposed. The citrus fruit waste contains several functional compounds, but the extraction of these functional compounds requires adequate production facilities. The waste is not suitable to carry for long distances due to the high percent of water content and its heavy weight, and it is not suitable to store for a long time due to the occurrence of fermentation. Some of the approaches target the use of waste in the proximity of the processing factories. The application of citrus fruit waste for crop production in the agricultural fields close to the faculties is one of the possible management options. The evidence of citrus fruit waste as herbicidal, nematocidal, insecticidal, and anti-fungal materials has been accumulated in the literature over three decades. Several compounds involved in these functions have also been identified in the citrus fruits. However, there has been no review article focusing on the pesticidal activity of citrus fruits against weeds, herbivore insects, parasitic nematodes, and pathogenic fungi. This is the first review article providing an overview of such activities and compounds involved in the functions of citrus fruits.